2020
DOI: 10.4274/balkanmedj.galenos.2020.2019.5.89
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of HIV-1 in the Presence of Hepatitis B Virus and Hepatitis C Virus Co-infections

Abstract: Background: Because of their similar modes of transmission, the simultaneous infection of viral hepatitis and human immunodeficiency virus are increasingly seen as a big problem related to human health. Aims: To determine the drug mutations in hepatitis B virus and/ or hepatitis C virus co-infected human immunodeficiency virus-1 patients in Turkey. Study Design: Retrospective cross-sectional study. Methods: The present study was conducted between 2010 and 2017. HBsAg, anti-hepatitis C virus, and anti-human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among 949 HIV-infected people from Istanbul, Turkey, HBsAg and anti-HCV seroprevalences were determined as 6.2% and 0.9%, respectively [23]. In another study evaluating serological data of 3,896 HIV-infected people across Turkey, HBV and HCV co-infections were reported as 3.2% and 0.5%, respectively [24]. Serological prevalence rates obtained in our study showed similarities with chronic viral hepatitis infection rates among the general population and other HIV-infected people in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Among 949 HIV-infected people from Istanbul, Turkey, HBsAg and anti-HCV seroprevalences were determined as 6.2% and 0.9%, respectively [23]. In another study evaluating serological data of 3,896 HIV-infected people across Turkey, HBV and HCV co-infections were reported as 3.2% and 0.5%, respectively [24]. Serological prevalence rates obtained in our study showed similarities with chronic viral hepatitis infection rates among the general population and other HIV-infected people in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 and hepatitis B virus (HBV) share common routes of transmission and therefore co-infection is common ( Sayan et al, 2020 ). HBV and HIV-1 can be transmitted to children through contaminated blood products or via vertical transmission ( Yeung and Roberts, 2001 ).…”
Section: Introductionmentioning
confidence: 99%